Effect of the parenting preparation program on maternal role competence: A systematic review and meta-analysis - Forough Talebi; Nahid Javadifar; Masoumeh Simbar; Maryam Dastoorpoor; Nahid Shahbazian; Zahra Abbaspoor (Wolters Kluwer Medknow Publications, 2023)
Background: The maternal sense of competence refers to the mother's sense of ability to care for the baby. Maternal competence can affect the mother's parenting capacities. Maternal preparation programs are aimed to increase mothers' knowledge and improve their maternal competence. This systematic review and meta-analysis investigated the effect of a maternal preparation program on maternal role competence. Materials and Methods: A systematic search was conducted using the following MeSH terms: "education", "program", and "parenting sense of competence" in databases including PubMed, Web of Science, Cochrane Central, and Scopus, from inception till July 2022. All Randomized Controlled Trials (RCTs) published in any language were extracted. Articles were screened based on predefined inclusion and exclusion criteria. The quality of the included articles was assessed by two qualified reviewers based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: Of the 170 published works that were retrieved in the initial stage, five articles including 647 first-time mothers were analyzed. A meta-analysis showed that parenting preparation program interventions increased maternal role competence in first-time mothers as opposed to those who received routine care Mean Difference (MD) = 3.31, 95% Confidence Interval (CI) [2.07, 4.55]. Conclusions: The results of this study encourage health policymakers to develop maternal preparation programs for first-time mothers and their children.